Pacing e fase do dia no ciclismo - Fernandes, Alan Lins (2013)
The pacing strategy is one of the main determinants of performance, despite with few evidences indicating the optimal pacing strategy for different kinds of race. Some factors such as circadian rhythm, hormonal and metabolic changes, alertness, mood, athlete’s initial conditions and environmental factors are able to directly interfering in pacing strategy result in a better performance, although the effects of day phases is unknown. Thus, the present dissertation presents two studies: the first is a narrative review with the aim to demonstrate data about the types of pacing, their regulatory mechanisms, and environmental and circadian factors. The second, an original article, aimed to investigate the effects of different phases of day (morning vs. evening) on pacing strategy, performance, physiological, metabolic and psychological responses during a 1000-m cycling time trial. As evidenced in the review article, the short term events usually begin and remain at high power output values throughout the race, characterized by an "all-out" pacing strategy. Moderate to long duration tasks tend to start with lower power output and keep either an average throughout the race (even pacing strategy), or increase (negative pacing strategy), or decrease (positive pacing strategy), or even present varied behaviors (parabolic or varied pacing strategy). The complex regulatory mechanisms of pacing strategy is based on the teleantecipation processes, so some of the environmental factors (e.g., temperature and oxygen content environment), motivational aspects and previous experiences represent components capable of exerting influence on the pacing strategy adopted and consequently, the end result. In the original article, nine recreational cyclists demonstrated a trend to reduce time to complete the task in the evening than in the morning. During the evening, they had higher concentrations of GH, which was accompanied by high levels of glucose, sublingual temperature and affectivity, and lower concentrations of cortisol, suggesting a more favorable environment for better performance. However, pacing strategy was similar between morning and evening. Based on these findings, the present dissertation shows evidence of improved performance in the evening, with some synchronous metabolic, physiological and psychological variations.